2018
DOI: 10.1177/0267323118793779
|View full text |Cite
|
Sign up to set email alerts
|

Using public opinion to serve journalistic narratives: Rethinking vox pops and live two-way reporting in five UK election campaigns (2009–2017)

Abstract: The power the media have to (re)define politics and privilege some views over others is striking during election campaigns. After all, the media assemble the actors involved in the contest and help dramatize it by how they construct campaign coverage. The focus of this study is the role played by citizens and journalists as sources, and the editorial construction of public opinion at election time. It carries out the largest ever study of sources to date across

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…Remarkably, the opposition’s sound bites also support the government’s side because they are either off-topic or ambiguous and the final sound bite makes the creators of the report ridiculous, finally the reporter cites the Foreign Minister in which he closes the issue by saying that he will send the detailed rebuttal to all items to all Members of the European Parliament. This confirms the findings of Cushion (2018) who investigated vox pops in the United Kingdom and found that sound bites serve journalistic narratives. This story exemplifies a well-built propaganda news story that may seem to be technically balanced (giving voice to all sides), but the story is built from facts and sounds in a way that the emerging discourse leaves little doubt that the EU’s allegations are unfounded.…”
Section: Analysis Of Framing and Discoursessupporting
confidence: 88%
“…Remarkably, the opposition’s sound bites also support the government’s side because they are either off-topic or ambiguous and the final sound bite makes the creators of the report ridiculous, finally the reporter cites the Foreign Minister in which he closes the issue by saying that he will send the detailed rebuttal to all items to all Members of the European Parliament. This confirms the findings of Cushion (2018) who investigated vox pops in the United Kingdom and found that sound bites serve journalistic narratives. This story exemplifies a well-built propaganda news story that may seem to be technically balanced (giving voice to all sides), but the story is built from facts and sounds in a way that the emerging discourse leaves little doubt that the EU’s allegations are unfounded.…”
Section: Analysis Of Framing and Discoursessupporting
confidence: 88%
“…Furthermore, the government supervision model cannot cope with the massive and growing amount of social and political news information obtained by the public from unofficial media, which provides the institutional possibilities for the negative impact of unofficial media on system confidence (Ariely, 2015;Zhang and Lin, 2018). More critically, access conditions (minimal barriers to entry, zero associated costs), rapid replication, information distortion and fabrication, users' inherent ability to comment on provided content, and lack of oversight overreporting methods (Cushion, 2018), along with the long-term repetitive and cumulative effects thereof (Gvirsman et al, 2016), provide an expanded mechanism for the negative influence of unofficial media on system confidence (Hu, 2002). Accordingly, we propose the following hypothesis:…”
Section: Impact Of Unofficial Media Use On System Confidencementioning
confidence: 99%
“…Research also shows how the affordances of the live two-way are used across news areas (election campaign reporting, foreign news, war journalism etc.) to produce authoritative interpretations, evaluations or speculations that reproduce ideological and moral frameworks and jeopardizes the impartiality of journalism (Cushion 2018;Smith and Higgins 2012).…”
Section: Epistemic Claim 3: the Articulation Of Epistemic Claims In Live News Broadcastingmentioning
confidence: 99%